2018
DOI: 10.1111/jph.12709
|View full text |Cite
|
Sign up to set email alerts
|

Using antagonistic soil bacteria and their cell‐free filtrates to control the black rot pathogen Xanthomonas campestris pv. campestris

Abstract: Xanthomonas campestris pv. campestris (Xcc) is a phytopathogenic bacteria, and it is the causative agent of black rot in crucifers. Recent studies have shown that Bacillus species have strong biological control on Xanthomonas. One of the mechanisms of this control is secondary metabolites production. A collection of 257 bacteria isolated from a suppressive soil was evaluated for in vitro antagonistic activity against X. campestris, and 92 isolates (44.6%) were able to inhibit its growth. Among the 92 isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
(19 reference statements)
0
8
0
3
Order By: Relevance
“…Other studies have shown that B. subtilis acts in the control of fungi of the genus Fusarium (Yesid et al, 2012;Mejía-Bautista et al, 2016;Da Silva et al, 2018). This Bacillus is an effective soil and rhizosphere colonizer with great genetic diversity (Montor-Antonio et al, 2014); which favors the antagonistic activity against pathogens and consequently induces the development of the plant.…”
Section: Rhizobacterial Antagonism On S Cepivorummentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that B. subtilis acts in the control of fungi of the genus Fusarium (Yesid et al, 2012;Mejía-Bautista et al, 2016;Da Silva et al, 2018). This Bacillus is an effective soil and rhizosphere colonizer with great genetic diversity (Montor-Antonio et al, 2014); which favors the antagonistic activity against pathogens and consequently induces the development of the plant.…”
Section: Rhizobacterial Antagonism On S Cepivorummentioning
confidence: 99%
“…In addition, Sánchez et al, (2016), record the production of Iturin A by these bacteria, such as fengicins that cause an osmotic imbalance in the spores and antifungal activity against the filaments of the fungus; Surfactin inhibits spore germination (Arjona-López, 2019) and the excretion of antimicrobial enzymes such as β-glucosidases and proteases that control leaf and root diseases (Da Silva et al, 2018). In studies with Pseudomonas fluorescens and B. subtilis they presented inhibition against fungi such as Rhizoctonia solani, Fusarium oxysporum, and Sclerotium sosfsii (Paredes Escalente et.…”
Section: B a Cmentioning
confidence: 99%
“…In 2018, the Fungicide Resistance Action Comittee (FRAC), listed Bacillus subtilis and B. amyloliquefaciens as producers of antifungal substances classified in group F. They act in the transportation or synthesis of lipids, affecting the function and integrity of the cell membranes of pathogens (FRAC, 2018). On the other hand, Sánchez et al (2016) reported that they are capable of producing iturines and phengicin that cause osmotic imbalances in spores and antifungal activity against filamentous fungi, along with surfactin, which inhibit the spore germination, excretion of antimicrobial enzymes such as β-glucosidases and proteases of fungi that cause leaf and root diseases (Da Silva et al, 2018). Some authors have proven the biocontrolling potential of B. subtilis in the control of the genus Fusarium (Mejía-Bautista et al, 2016), Rhizoctonia solani, Fusarium oxysporum, Sclerotium rolfsii (Paredes-Escalente et al, 2009), and other.…”
Section: Fully Bilingualmentioning
confidence: 99%
“…In the case of B. amyloliquefaciens, it has antimicrobial capacity and it induces a defensive response in plants (Soto et al, 2018 (FRAC, 2018). Por otra parte, Sánchez et al (2016), reportaron que son capaces de producir iturinas y fengicinas que causan desequilibrios osmótico en las esporas y actividad antifúngica contra hongos filamentosos, además de surfactina que inhiben la germinación de las esporas, excreción de enzimas antimicrobianas como β-glucosidasas y proteasas de hongos causantes de enfermedades foliares y de raíces (Da Silva et al, 2018). Algunos autores han demostrado el potencial biocontrolador de B. subtilis, en el control del géneros Fusarium (Mejía-Bautista et al, 2016), Rhizoctonia solani, Fusarium oxysporum, Sclerotium rolfsii (Paredes-Escalente et al, 2009), entre otros.…”
Section: Fully Bilingualunclassified
“…The bacterial endophytes used in this study are preserved in the Microorganisms Collection of the Laboratory of Agriculture Microbiology of The Center of Agrarian Sciences of the Federal University of Alagoas. The endophytes were selected in according to his hability of solubilize inorganic phosphate in previous study by Silva et al (2018). All the bactetial endophytes (ISO31, ISO33, ISO34, ISO48 e ISO51) are from the Bacillus genre.…”
Section: Bacterial Endophytesmentioning
confidence: 99%